The answer should actually be
Log (base 4) ^27
Please help simplify this expression:
2 log (base 4) ^9 - log (base 2) ^3
The answer should be
log(base 2) ^3
2 answers
Note that since 4 = 2^2, log_2(x) = 2log_4(x)
That is, 4^n = 2^2n
So, we have
2log_4(9) - log_2(3)
= log_2(9) - log_2(3)
= log_2(9/3)
= log_2(3)
Not sure where you got log_4(27). If that's the solution given, it is bogus.
That is, 4^n = 2^2n
So, we have
2log_4(9) - log_2(3)
= log_2(9) - log_2(3)
= log_2(9/3)
= log_2(3)
Not sure where you got log_4(27). If that's the solution given, it is bogus.